2018
DOI: 10.4102/sajhrm.v16i0.1001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating cyberloafing, organisational justice, work engagement and organisational trust of South African retail and manufacturing employees

Abstract: Orientation: Understanding cyberloafing, organisational justice, work engagement and organisational trust will lead organisations to develop strategies to counter the consequences of cyberloafing.Research purpose: This research explored the relationships between cyberloafing, organisational justice, work engagement and organisational trust among South African office workers in the retail and manufacturing industry.Motivation for the study: Cyberloafing, a prevalent way for office employees to engage in non-wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
(105 reference statements)
1
15
0
2
Order By: Relevance
“…Employees will work extra and strive for something to work above what is expected, both in time and energy (Schaufeli et al, 2006). Oosthuizen et al (2018) On a study of 2500 workers in manufacturing companies, Ning etal. (2007) showing a positive correlation between organizational trust and task performance.…”
Section: Motivation Work Engagement Task Performancementioning
confidence: 99%
“…Employees will work extra and strive for something to work above what is expected, both in time and energy (Schaufeli et al, 2006). Oosthuizen et al (2018) On a study of 2500 workers in manufacturing companies, Ning etal. (2007) showing a positive correlation between organizational trust and task performance.…”
Section: Motivation Work Engagement Task Performancementioning
confidence: 99%
“…A study also shows that workplace ostracism has a positive relationship with cyberloafing and emotional exhaustion is a mediating factor (Koay, 2018). Another study indicates that when organizations are fair towards employees, it creates organizational trust and leads to higher employee engagement which consequently reduces cyberloafing behavior among employees (Oosthuizen, Rabie, & Beer, 2018). The researcher reported that employees who like their job would tend to spend less time on irrelevant activities such as internet abuse (Rezayian, 1995).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Past studies explored that intrinsic motivation factors, i.e. Effective commitment (Usman et al, 2019), organizational commitment (Oosthuizen et al, 2018), Psychological capital (Agrawal, 2019), and involvement (Liberman et al, 2011) have negative associations with cyberloafing. Similarly, prior studies on supervisor behaviour show its positive effect on job outcomes, employee job satisfaction, work engagement, work performance, and followers' attitudes and behaviours, but up to the researcher's knowledge, the link between supervisor communication styles and cyberloafing is very rare.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…As rightly noted by Koay, 2018and de-Lara andViera-Armas, (2017), that deterring cyberloafing through formal control mechanisms and punishments may increase cyberloafing practices because it's human psychology that individuals involved in those activities which are prohibited by laws or rules, use it as a means of counter-behaviour (Hu and Hsu, 2015). Thus, to effectively deter cyberloafing activities, organizations must focus on employees' intrinsic motivations, a possible tool for deterring cyberloafing activities (Oosthuizen et al, 2018). Regardless the apparent destructive upshots of cyberloafing for an employee as well as organizations and the importance of focusing on employee's intrinsic motivation for discouraging cyberloafing, only a few studies highlight the link between intrinsic motivation related factors and cyberloafing, (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation